2000
DOI: 10.1590/s0004-282x2000000300007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e impacto da migrânea em funcionários do Hospital das Clínicas da Faculdade de Medicina de Ribeirão Preto - USP

Abstract: RESUMO -Cefaléia é sintoma comum na população, com prevalência ao longo da vida superior a 90%. Acarreta importante impacto na qualidade de vida de seus portadores. O presente estudo tem por objetivo avaliar a prevalência da migrânea entre trabalhadores de um hospital universitário, bem como mensurar a intensidade, interferência e impacto dela em algumas atividades cotidianas. Um total de 1890 funcionários respondeu a questionário que possibilitava o diagnóstico da migrânea. A prevalência dessa cefaléia ao lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0
12

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 16 publications
1
18
0
12
Order By: Relevance
“…Migraine has also been the most frequent headache type found in studies performed in Brazilian tertiary-care centers, ranging from 38 to 45.1% 2,6,7 . It is important to note that the patients selected in the present study sought medical care spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Migraine has also been the most frequent headache type found in studies performed in Brazilian tertiary-care centers, ranging from 38 to 45.1% 2,6,7 . It is important to note that the patients selected in the present study sought medical care spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Employees from the University of São Paulo at Ribeirão Preto Medical School Hospital das Clínicas in the State of São Paulo said that they avoid driving when in pain (35.1%); some reported about having canceled family (59.9%) and leisure activities (81.2%) due to pain. Eighty-two percent reported that they had to stop doing what they were doing to lie down or that they would like to lie down (3) .…”
Section: Discussionmentioning
confidence: 99%
“…Headaches are less common in the population compared to other country studies, and they affect the students' everyday activities. Headache is a frequent complaint among young students and the losses this pain causes implies disability, educational failure and an average absenteeism rate of 2.8 days/year (1) , greater vulnerability to comorbidities (2) and impaired quality of life (3) . A consensus exists that women and young adults are the most represented cases (4) .…”
Section: Introductionmentioning
confidence: 99%
“…27 A study conducted at the University Hospital of Ribeirão Preto estimated a loss of approximately 500,000 dollars in a single year due to the reduced productivity of its employees during migraine crises. 15 Even though impairment of work was reported, absenteeism was not frequent (8.7%) among the participants; 90% of those who reported missing work due to headache belonged to the migraine group. Headache also generated loss of productivity, even when the employees went to work with a headache.…”
mentioning
confidence: 83%
“…This result is similar to the findings of Bigal et al, who observed a crisis frequency of two to four times a month in 47% of the employees with migraine. 15 Very frequent crises (occurring on more than 15 days per month) characterize a group of headaches called chronic daily headache (CDH). 16 The presence of CDH affects the quality of life, with an important impact on individuals' productive, social and emotional characteristics.…”
mentioning
confidence: 99%